Unsteady axisymmetric hybrid graphene-copper nanofluid slip flow over a permeable radially shrinking disk with the Soret and Dufour effects - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi'ie, Najiyah Safwa; Pop, Ioan (Elsevier B.V., 2024)
This study investigates the unsteady axisymmetric flow of a hybrid graphene-copper nanofluid over a permeable radially shrinking disk, accounting for velocity slip, Dufour, and Soret effects. Examining such boundary layer flows of hybrid nanofluids is crucial for understanding the underlying fluid mechanics and thermophysical behavior. The fluid flow model is solved using a finite difference scheme in MATLAB to generate the numerical solutions. Since dual solutions are attainable, stability analysis is performed to analyze the nature of the solutions. The existence of dual solutions enables exploring flow separation dynamics through selected control parameters. Results indicate that higher copper volume fraction and velocity slip effectively prevent the boundary layer separation. The 2 % copper volume fraction delays the boundary layer separation approximately 6 % better compared to the usage of 1 % copper volume fraction. The heat transfer is improvable by reducing the shrinking intensity of the disk and maximizing the velocity slip and Soret parameters. The comprehensive mathematical model presented herein lay a solid foundation for future research endeavors, particularly in the field of hybrid nanofluids and their applications in thermal management systems.